Wealth Accumulation and De‐Risking Strategies Among High‐Wealth Individuals - Donna Carmichael (Social Inclusion, 2023)
The emergence of the asset economy in advanced capitalist countries has enabled significant asset accumulation by high‐wealth individuals, and the rise of finance has provided new, profitable investment vehicles for those with investable capital. This accumulation process has been described as a form of compensatory logic to achieve protection from future risks, especially in the current neoliberal environment with governments reducing state pensions while promoting tax‐deductible private investments as a substitute for state provision. This article reports the results of qualitative research into the private wealth accumulation attitudes and behaviours of high‐wealth individuals and their worries about achieving a comfortable retirement despite their substantial wealth holdings. Although the interviewees reside within the top 5% of the wealth distribution in the UK and would be expected to feel confident that their wealth will be sufficient to support their retirement needs, they convey a sense of uneasiness and concern that they will still not have enough to support their expected retirement lifestyles. In response to this perceived risk, these high‐wealth individuals engage in a variety of what I call “de‐risking” behaviours with the goal of mitigating the risk of insufficient wealth to support retirement. The article contributes to our understanding of the processes utilised by high‐wealth individuals to help ensure they have sufficient wealth to support their desired comfortable retirement by engaging in strategies intended to de‐risk their financial lives.